2014
DOI: 10.1007/s13277-014-2535-3
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 promotes cellular proliferation and invasion, suppresses cellular apoptosis in osteosarcoma

Abstract: Osteosarcoma is the most common primary malignant bone tumor in children and adolescents. Unfortunately, treatment failures are common due to the metastasis and chemoresistance, but the underlying molecular mechanism remains unclear. Accumulating evidence indicated that the deregulation of DNA-binding protein high-mobility group box 1 (HMGB1) was associated with the development of cancer. This study aimed to explore the expression of HMGB1 in osteosarcoma tissues and its correlation to the clinical pathology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Additionally, HMGB proteins are subdivided into HMGB1, HMGB2, and HMGB3, all of which contain two HMG-box domains and a highly acidic Cterminal tail [10,11]. The current study found the expression levels of HMGB1 gene were significantly higher than that of the corresponding normal tissues in a variety of tumor tissues, including colorectal cancer, breast cancer, pancreatic cancer, melanoma, et al, which suggested that HMGB1 was involved in the occurrence and development of tumors [12][13][14][15][16]. Dong found that knockdown of the HMGB1 expression inhibited tumor growth and metastasis in human liver cancer through AKT-mediated regulation of Ki-67 and MMP-2 expression [17].…”
Section: Introductionsupporting
confidence: 48%
“…Additionally, HMGB proteins are subdivided into HMGB1, HMGB2, and HMGB3, all of which contain two HMG-box domains and a highly acidic Cterminal tail [10,11]. The current study found the expression levels of HMGB1 gene were significantly higher than that of the corresponding normal tissues in a variety of tumor tissues, including colorectal cancer, breast cancer, pancreatic cancer, melanoma, et al, which suggested that HMGB1 was involved in the occurrence and development of tumors [12][13][14][15][16]. Dong found that knockdown of the HMGB1 expression inhibited tumor growth and metastasis in human liver cancer through AKT-mediated regulation of Ki-67 and MMP-2 expression [17].…”
Section: Introductionsupporting
confidence: 48%
“…Previous studies showed that the increased expression of HMGB1 in many malignant tumors has been associated with progressive tumor proliferation, invasion, metastasis, and poor prognosis, for example, hepatocellular carcinoma, osteosarcoma, bladder cancer, gastric cancer, colon cancer, breast cancer, and mesothelioma. [70][71][72][73][74][75][76][77][78][79][80] Besides, the overexpression of HMGB1 was closely related to the level of tumor invasion and the stage of lymph node metastasis in colon and colorectal cancer. 81 Of note, the overexpression of HMGB1, TLR4, and MyD88 are correlated with tumor-node-metastasis stage and lymph node metastasis in gastric cancer, which proves poor prognosis.…”
Section: Oncogenic Roles In Tumorigenesismentioning
confidence: 99%
“…Previous studies have reported that high-mobility group box 1 protein (HMGB1) was a critical factor in the development of chemoresistance (14)(15)(16), and notably, that it promoted drug resistance in osteosarcoma, thus suggesting a novel target for improving osteosarcoma therapy (15,(17)(18)(19). Recently, Meng et al (20) observed that the tumorigenesis, invasion and metastasis of osteosarcoma was associated with overexpression of HMGB1, which may thus be a potential target for treatment (20). However, to the best of our knowledge, it has not been clarified whether HMGB1 is involved in cell necrosis during the development and progression of osteosarcomas.…”
Section: Introductionmentioning
confidence: 99%